2017
DOI: 10.1016/j.joca.2017.02.772
|View full text |Cite
|
Sign up to set email alerts
|

Knee osteoarthritis and the risk of premature mortality in the community: An international individual patient level meta-analysis in 9889 subjects

Abstract: sensitization/pain sensitivity; at a site of disease (e.g., knee), it indicates peripheral sensitization, and at a site without disease (e.g., wrist), it indicates central sensitization. The Intermittent and Constant OA Pain (ICOAP) instrument assesses presence and severity of intermittent and constant pain, and for intermittent pain, its frequency. Using the knee-specific ICOAP, pain patterns were defined as: 1) no intermittent or constant pain; 2) intermittent pain only (of at least mild severity occurring a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Veronese et al [8][9][10] performed a meta-analysis of the literature and found that hip or knee OA was associated with increased mortality (HR 1.18[95% CI 1.08-1.28]). 8 This study also found that hip or knee OA was associated with a 21% increase in cardiovascular mortality.…”
mentioning
confidence: 99%
“…Veronese et al [8][9][10] performed a meta-analysis of the literature and found that hip or knee OA was associated with increased mortality (HR 1.18[95% CI 1.08-1.28]). 8 This study also found that hip or knee OA was associated with a 21% increase in cardiovascular mortality.…”
mentioning
confidence: 99%